Lights and Shadows of Trait Emotional Intelligence: Its Mediating Role in the Relationship Between Negative Affect and State Anxiety in University Students - Guil, Rocio; Gómez-Molinero, Rocio; Merchán-Clavellino, Ana; Gil-Olarte, Paloma (Frontiers in Psychology, 2021)
Nowadays students are experiencing difficult and stressful situations due to the Global Pandemic Alert. This changing world can evoke negative emotions that have been traditionally linked to higher anxiety. Researches have been focused on the positive outcomes of trait emotional intelligence (TEI) preventing psychological disorders. However, it has been neglected the possibility that TEI might have a dark side. Hence, the purpose of this study was to explore the mediating effect of the three dimensions of TEI in the relationship between negative affect and anxiety symptoms among college students. Participants of this research were 467 undergraduates who completed an online self-reported questionnaire including the Positive and Negative Affect Schedule (PANAS; Sandín et al., 1999), the State-Trait Anxiety Inventory (STAI; Spielberger, Gorsuch, Luchene, Vagg, and Jacobs, 1983), and Trait Meta-Mood Scale (TMMS-24, Extremera, and Fernández-Berrocal, 2002). The serial mediation analysis revealed that the total amount of variance explained by the global model was 30.8% (R² = .31). The analysis showed that negative affect and age accounted for the 15.1% of state anxiety variance (R² = .15; c: B = .63, p < .001). Moreover, 15.7% of the variance of state anxiety was attributed to the direct or indirect effect of the three dimensions of TEI (R² = .16). Five indirect effects presented statistical significance (95% BootCI). The contrast analyses between mediators showed that three indirect effects had higher statistical weigh; the ability of negative affect to increase state anxiety through i) emotional attention; ii) emotional clarity, and iii) serially through emotional clarity and mood repair. Our results indicated that students’ negative emotions lead to higher emotional attention what in turn may enhance state anxiety in two ways: by a direct effect of emotional attention on state anxiety and by a serial effect through emotional clarity. Moreover, when negative affect is associated with lower emotional clarity anxiety symptoms may also arise. However, when attention and clarity are connected the negative effect is reversed into a positive one, decreasing state anxiety.